Physcochemical and Functional Characteristics of Banana and Potato Starches With Heat Moisture Treatment (HMT) and Its Effect to The Change of Physical and Sensory Characteristics of Instant Potato Starch Bihoon - Dessy Wiriani; Herla Rusmarilin; Era Yusraini (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Bihun were usually made from rice flour. Rice is Indonesian’s staple of food which high needs. In other to solve the problems, food diversification is done by replacing bihoon raw materials with banana and potato. The aim of this research was to study the physcochemical and functional characteristics of banana and potato starches with Heat Moisture Treatment (HMT) and their effect on the physical and sensory characteristics of resulted instant bihoon.The research was conducted in three phases i.e firstly, the manufacture of natural starch. The starch was analyzed for the moisture content, ash content, starch content, water absorption, oil absorption, cold water-solved ability, the clarity of pasta, color, amylase content, and secondly, the making of corn flour with parameters the moisture content, ash content, protein content, fat content, fiber content, and color. Thirdly, the manufacture of instant bihoon made from composite flour with parameters for the bihoon characteristics as the optimum cooking time, color, organoleptic test of color, flavor and taste. The results showed that the physcochemical and functional characteristics value of banana and potato starches with HMT in overall had a lower value compared to its natural starch, except to the value of water absorption and oil absorption. The results showed that interaction of the ratio of banana and potato starch with carragenan had a highly significant effect (P<0,01) on color (a) value but had no effect (P>0,05) on the optimum cooking time, color (L), color (b), and organoleptic test of color, flavor and taste. Keywords : banana starch, carragenan, Heat Moisture Treatment (HMT), potato starch